2021
DOI: 10.3390/metabo11110738
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Causal Relations between Steroid Hormones and Obesity—A Mendelian Randomization Study

Abstract: Steroid hormones act as important regulators of physiological processes including gene expression. They provide possible mechanistic explanations of observed sex-dimorphisms in obesity and coronary artery disease (CAD). Here, we aim to unravel causal relationships between steroid hormones, obesity, and CAD in a sex-specific manner. In genome-wide meta-analyses of four steroid hormone levels and one hormone ratio, we identified 17 genome-wide significant loci of which 11 were novel. Among loci, seven were femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Single nucleotide polymorphisms (SNPs) predicting levels of five steroid hormones were obtained from the GWAS by Pott et al. ( 18 ). This GWAS used data from LIFE-Adult (males/females: 863/618) ( 21 ) and LIFE-Heart (males/females: 1357/711) ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Single nucleotide polymorphisms (SNPs) predicting levels of five steroid hormones were obtained from the GWAS by Pott et al. ( 18 ). This GWAS used data from LIFE-Adult (males/females: 863/618) ( 21 ) and LIFE-Heart (males/females: 1357/711) ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…We want to acknowledge the participants and investigators of the GWAS from Pott et al. ( 18 ), FinnGen study ( ), the GWAS from Winkler et al. ( 24 ) and MRC-IEU consortium for sharing the genetic data.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen is effective in maintaining the integrity of the oral cavity as well as regulating reproductive functions. 30 High estrogen levels in patients with PCOS affect the vascular permeability of the oral mucosa, which reduces the immune competence of the oral cavity. 31 Zhang et al 32 found that estrogen was present in the cells in the salivary gland ducts and suggested that the salivary glands were one of the estrogen target organs.…”
Section: Discussionmentioning
confidence: 99%
“…Data on A4 and T/E2 were obtained from a GWAS ( 17 ) consisting of 3,549 European samples from LIFE-Adult ( 18 ) and LIFE-Heart ( 19 ). This GWAS used liquid chromatography–tandem mass spectrometry to quantitatively determine A4 levels and employed the electrochemiluminescence immunoassay to quantitatively study both T and E2.…”
Section: Methodsmentioning
confidence: 99%